2003
DOI: 10.1128/aem.69.5.2748-2754.2003
|View full text |Cite
|
Sign up to set email alerts
|

Homologous npdGI Genes in 2,4-Dinitrophenol- and 4-Nitrophenol-Degrading Rhodococcus spp

Abstract: Rhodococcus (opacus) erythropolis HL PM-1 grows on 2,4,6-trinitrophenol or 2,4-dinitrophenol (2,4-DNP) as a sole nitrogen source. The NADPH-dependent F 420 reductase (NDFR; encoded by npdG) and the hydride transferase II (HTII; encoded by npdI) of the strain were previously shown to convert both nitrophenols to their respective hydride Meisenheimer complexes. In the present study, npdG and npdI were amplified from six 2,4-DNP degrading Rhodococcus spp. The genes showed sequence similarities of 86 to 99% to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…The hydride transferases that mediate these reactions share approximately 30% amino acid sequence identity with Mtd of methanogens (435). The results of comparative genomics suggest that homologs of these proteins are exclusively encoded by the genera Nocardioides, Rhodococcus, and Nocardia among presently sequenced organisms.…”
Section: Fdors: Flavin/deazaflavin Oxidoreductase Superfamilymentioning
confidence: 91%
“…The hydride transferases that mediate these reactions share approximately 30% amino acid sequence identity with Mtd of methanogens (435). The results of comparative genomics suggest that homologs of these proteins are exclusively encoded by the genera Nocardioides, Rhodococcus, and Nocardia among presently sequenced organisms.…”
Section: Fdors: Flavin/deazaflavin Oxidoreductase Superfamilymentioning
confidence: 91%
“…Construction of the plasmids was carried out as follows: three transcriptional terminators (rrnB genes) of plasmid pDMW7 (25), a plasmid based on pBAD/Thio-TOPO (Invitrogen), were amplified using the primers rrnB_fwd_NsiI and rrnB_rev_NsiI and cloned into the NsiI site of pBBR1MCS-2-P BAD -phaM-eyfp (13), a plasmid based on pBBR1MCS-2 which harbors the P BAD promoter originally amplified from pDMW7, to minimize background expression of fluorescent fusion proteins during noninduced culture conditions from upstream-located promoters (e.g., kanamycin resistance gene). The orientation of the terminator fragments was checked by colony PCR and DNA sequencing; only constructs with desired orientations were used.…”
Section: Methodsmentioning
confidence: 99%
“…This bacterium can degrade not only mono-NPs, including 4-NP, but also poly-NPs, such as 2,4-dinitrophenol and 2,4,6-trinitrophenol (picric acid) (1). Analyses of the metabolites in NP degradation revealed that PN1 degrades 4-NP through the 4-NC pathway, whereas it also degrades 2,4-dinitrophenol and picric acid via the corresponding hydride-Meisenheimer complexes (1,13,44). Thus, PN1 has at least two quite different pathways for NP degradation.…”
mentioning
confidence: 99%
“…Thus, PN1 has at least two quite different pathways for NP degradation. The gene clusters involved in 4-NP degradation and picric acid degradation have been independently cloned from PN1 (13,43). The gene cluster encoding 4-NP oxidation consists of three genes, nphR, nphA1, and nphA2, which were expected from the deduced amino acid sequences to encode an AraC/XylS family regulatory protein (9) and a 4-NP hydroxylase belonging to the two-component flavin-diffusible monooxygenase (TC-FDM) family (8,43).…”
mentioning
confidence: 99%